ANALISIS PENGARUH LDR, NIM DAN BOPO TERHADAP ROA PADA SEKTOR PERBANKAN YANG TERDAFTAR DI BURSA EFEK INDONESIA PERIODE 2005-2009 - Sandra B11106087, Umi Rifqiyati (Jurnal Manajemen Update, 2013)
This study aimed to examine whether there is a significant effect of the Loan to Deposit Ratio (LDR), Net Interest Margin (NIM) and Operating Expenses to Operating Income (BOPO), either partially or simultaneously on Return On Assets (ROA). The data used in this study were obtained from Published Financial Statements of Banking Companies Listed on the Stock Exchange in the period 2005 to 2009. The number of the study population was 29 and the number of sample companies 8 companies with the passing stage purposive sampling. The research method used is descriptive method in the form of case studies. The analysis technique used is multiple linear regression and hypothesis testing using t-statistics for testing the partial regression coefficients and F-statistics to test the effect together with the level of significance of 5%. From the results of the regression analysis can be concluded that the partial, LDR variable has no significant effect on ROA, while the NIM and BOPO variables have a significant effect on ROA. Simultaneously, the three independent variables, namely LDR, NIM and BOPO has a significant influence on ROA. Predictive ability of these three variables on ROA bank at 81.8%, while the remaining 18.2% is influenced by other factors not included in the research model. The results of this study it is expected that the variable Loan to Deposit Ratio (LDR), Net Interest Margin (NIM) and Operating Expenses to Operating Income (BOPO) can be used as a guide, either by the management company in the management of the company, as well as by investors in determining the investment strategy. Keywords : Loan to Deposit Ratio (LDR), Net Interest Margin (NIM) and Operating Expenses to Operating Income (BOPO) and Return On Assets (ROA)